1936
DOI: 10.1172/jci100792
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Studies of the Changes in Body Electrolyte and Distribution of Body Water Induced Experimentally by Deficit of Extracellular Electrolyte 1

Abstract: The immediate effects of removing extracellular electrolyte from animals without changing the total quantity of body water were described in a recent publication (1). The clinical evidences of dehydration which occurred were shown to be brought about by the shift of water from the extracellular to intracellular fluids.In the present investigations the depletion of extracellular electrolyte was allowed to persist for seven days. The mechanism of adjustment was studied by frequent blood analyses and determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1937
1937
1961
1961

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…As suggested by other reports (1,13,14), animals depleted of sodium developed a negative nitrogen balance which was more pronounced than that observed in controls ( Figure 5). Net urinary losses of potassium in the two groups was similar and proportional to net losses of nitrogen WT. gm.. in the approximate ratio of 3 mEq of potassium to 1 g of nitrogen.…”
Section: Methodssupporting
confidence: 85%
“…As suggested by other reports (1,13,14), animals depleted of sodium developed a negative nitrogen balance which was more pronounced than that observed in controls ( Figure 5). Net urinary losses of potassium in the two groups was similar and proportional to net losses of nitrogen WT. gm.. in the approximate ratio of 3 mEq of potassium to 1 g of nitrogen.…”
Section: Methodssupporting
confidence: 85%
“…It has been described in experiments with water deprivation in the rabbit (14). 96 In man, it follows the ingestion of dry sodium chloride (15); in the dog, it follows the intravenous infusion of hypertonic sodium sulfate (16) and the injection of hypertonic saline in animals previously depleted of sodium and chloride (17).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments support earlier work demonstrating that the fall of sodium in scalded cats could be prevented if the blood vessels to the injured area were occluded (22). On the basis of these studies it has been suggested (20) that the diminished plasma volume in burn and traumatic shock is due to a systemic sodium depletion, analogous to that produced experimentally by loss of electrolytes into the peritoneal cavity (23), rather than to a loss of circulating plasma protein.…”
Section: Discussionmentioning
confidence: 99%